2017
DOI: 10.1094/mpmi-08-16-0156-r
|View full text |Cite
|
Sign up to set email alerts
|

Changing Ploidy as a Strategy: The Irish Potato Famine Pathogen Shifts Ploidy in Relation to Its Sexuality

Abstract: The oomycete Phytophthora infestans was the causal agent of the Irish Great Famine and is a recurring threat to global food security. The pathogen can reproduce both sexually and asexually, with high potential to adapt to various environments and great risk to break disease resistance genes in potato. As are other oomycetes, P. infestans is regarded to be diploid during the vegetative phase of its life cycle, although some studies reported trisomy and polyploidy. Using microsatellite fingerprinting, genome-wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 33 publications
8
77
0
Order By: Relevance
“…It has been suggested that cold winters, such as in Scandinavia, may favour sexual reproduction due to the more durable structures of the sexually produced oospores which can survive in the soil (Sjöholm et al , ); however, there have been many instances reported of self‐fertile P. infestans individuals that do not require sex to produce oospores (Campbell et al , ; Han et al , ; Pipe et al , ; Shattock et al , ; Smart et al , ; Tantius et al , ). The findings of Li et al () that diploidy can be induced using metalaxyl suggest that the maintenance of sex may not have to do with the durable resting structures produced after all, but rather the increased ability to adapt to all nature of stresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that cold winters, such as in Scandinavia, may favour sexual reproduction due to the more durable structures of the sexually produced oospores which can survive in the soil (Sjöholm et al , ); however, there have been many instances reported of self‐fertile P. infestans individuals that do not require sex to produce oospores (Campbell et al , ; Han et al , ; Pipe et al , ; Shattock et al , ; Smart et al , ; Tantius et al , ). The findings of Li et al () that diploidy can be induced using metalaxyl suggest that the maintenance of sex may not have to do with the durable resting structures produced after all, but rather the increased ability to adapt to all nature of stresses.…”
Section: Discussionmentioning
confidence: 99%
“…), are only expected for populations with extreme rates of clonality (Balloux et al , ) due to the accumulation of mutations through successive rounds of asexual reproduction. Li et al () found that in samples that changed from triploid to diploid under stress conditions, heterozygosity was maintained at the higher triploid level in the newly formed diploids. However, if the switch to diploidy accompanied a switch to sexual reproduction, recombination would act as homogenizing force over time, decreasing heterozygosity and bringing the F IS rapidly back to zero (Balloux et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of the corresponding mutations was not investigated in all organisms, different mutations of RPA190 in yeast did lead to different phenotypes such as N1203S and L1222S . Recently, it was reported that triploids might be common in asexual lineages of P. infestans . This genetic mode may affect the accumulative pattern of metalaxyl resistance to a certain extent.…”
Section: Discussionmentioning
confidence: 60%
“…44 Recently, it was reported that triploids might be common in asexual lineages of P. infestans. 45 This genetic mode may affect the accumulative pattern of metalaxyl resistance to a certain extent. Nevertheless, the findings of the current study offer insight into the inherited nature of metalaxyl resistance in P. infestans.…”
Section: Discussionmentioning
confidence: 99%
“…New, recombined strains may adapt to environmental changes, resistant hosts or application of fungicides, and then spread. Li et al (2017) showed that asexual clonal lineages of P. infestans, which are often triploid, in stress conditions can change to a diploid genome constitution. The triploid genotypes are more heterozygous than diploid and preserve more genetic differences.…”
Section: Introductionmentioning
confidence: 99%